PEMBANGUNAN FUZZY INFERENSI SISTEM UNTUK PENENTUAN KUALITAS AGEN HAYATI - Ratnawati, Ratnawati; Pahlevi, Said Mirza (STMIK ANTAR BANGSA, 2016)
Abstract—Agriculture is an important sector in the people's livelihood. One of the government's attention on this sector is to establish a Balai Besar Peramalan Organisme Pengganggu Tumbuhan (BBPOPT). The task of BBPOPT is to observe and become the center of forecasting the development of plant pests. One of the results of its research is to reproduce the kind of biological agent biopesticide products containing microorganisms as the active ingredient. Besides reproduced, these biological agents are also distributed to areas in need throughout Indonesia. But unfortunately, the media that can be used to assess the quality of biological agents that have been deployed and even reproduced in a variety of the area is still very limited. This study examines and builds a Fuzzy Inference System (FIS) as a medium for the determination of the quality of biological agents. From the results of the study, FIS is built with five input variables based on the dimensions of product quality, that is, performance, reliability, conformance, features, and durability. From the evaluation results with expert assessment, it was found that the FIS can be used to determine the quality assessment of biological agents with the degree of accuracy of 71.4 percents.Intisari—Pertanian merupakan sektor penting dalam mata pencaharian masyarakat. Perhatian pemerintah pada sektor ini salah satunya adalah dengan dibentuknya Balai Besar Peramalan Organisme Pengganggu Tumbuhan (BBPOPT). Salah satu hasil pengembangannya adalah dengan memperbanyak agen hayati yakni jenis produk biopestisida yang mengandung mikroorganisme sebagai bahan aktifnya. Namun sayangnya media yang dapat digunakan untuk menilai kualitas agen hayati yang sudah disebarkan dan bahkan sudah diperbanyak di berbagai daerah tersebut masih sangat terbatas. Penelitian ini mengkaji dan membangun sebuah Fuzzy Inference System (FIS) sebagai media untuk penentuan kualitas agen hayati. Dari hasil kajian, FIS dibangun dengan lima variabel input berdasarkan dimensi kualitas produk yaitu kinerja, keandalan, kesesuaian, fitur, dan keawetan. Dari hasil evaluasi dengan penilaian pakar, didapatkan bahwa FIS yang dibangun telah dapat digunakan untuk menentukan penilaian kualitas agen hayati dengan tingkat keakuratan sebesar 71,4 persen.Kata Kunci— Agen Hayati, Fuzzy Inferensi System, Dimensi Kualitas.